Pengetahuan remaja putri tentang kesehatan reproduksi dengan status gizi remaja - Hanik Malikhatin; Christina Pernatun Kismoyo; Masyi Wimmy Johandika (Sekolah Tinggi Ilmu Kesehatan AKBIDYO, 2019)
Background: The age of adolescents is the most vulnerable age to experience reproductive health problems. Basic Health Research Results (2013) showed in DIY the prevalence of adolescents with malnutrition status was 2.4%, underweight nutrition at 4.9%, and obesity by 4.2%. The health status of today's adolescents will determine the picture of the health status of the adult population in the following decade, therefore adolescent health occupies an important position on a global scale.Objective: To find out the relationship between the knowledge of young women about reproductive health and nutritional status in SMA Negeri 1 Srandakan.Research Methods: Quantitative research, with analytic survey design, cross-sectional approach, population 148 and samples taken 66 using stratified random sampling techniques, data collection tools using questionnaires, univariate analysis with frequency distribution and bivariate analysis using Kendal-tau.Results: Knowledge of young women about reproductive health with a good category (53.1%) with normal nutritional status. Knowledge of good categories (34.7%) with underweight nutritional status and good level of adolescent knowledge (12.2%) with overweight nutritional status. There is no significant relationship between the level of knowledge of reproductive health with adolescent nutritional status p-value (0.313)> significant level (0.05).Conclusion: There is no relationship between the knowledge of young women about reproductive health and nutritional status in SMA Negeri 1 Srandakan INTISARI Latar Belakang: Usia remaja merupakan usia paling rawan mengalami masalah kesehatan reproduksi. Hasil Riset Kesehatan Dasar (2013) menunjukkan di DIY prevalensi remaja dengan status gizi kurang sebesar 2,4%, gizi kurus sebesar 4,9%, dan obesitas sebesar 4,2%. Status kesehatan remaja masa kini akan menentukan gambaran status kesehatan penduduk dewasa dalam dekade berikutnya, oleh sebab itu kesehatan remaja menempati posisi penting dalam skala global.Tujuan: Untuk mengetahui hubungan pengetahuan remaja putri tentang kesehatan reproduksi dengan status gizi di SMA Negeri 1 Srandakan.Metode Penelitian: Penelitian kuantitatif, dengan rancangan survey analitik, pendekatan cross-sectional, jumlah populasi 148 dan sampel yang diambil 66 menggunakan teknik stratified random sampling, alat pengumpulan data menggunakan kuesioner, analisis univariat dengan distribusi frekuensi dan analisis bivariat menggunakan Kendal-tau.Hasil : Pengetahuan remaja putri tentang kesehatan reproduksi dengan kategori baik (53,1%) dengan status gizi normal. Pengetahuan kategori baik (34,7%) dengan status gizi kurus dan tingkat pengetahuan remaja baik (12,2%) dengan status gizi gemuk. Tidak terdapat hubungan yang bermakna antara tingkat pengetahuan kesehatan reproduksi dengan status gizi remaja p-value (0,313) > taraf signifikan (0,05).Kesimpulan: Tidak ada hubungan antara pengetahuan remaja putri tentang kesehatan reproduksi dengan status gizi di SMA Negeri 1 Srandakan.